Fabrication and evaluation of taste masking sachets of tizanidine HCL - YV Ram Teja; K Sudhamani (International Journal of Pharmacy and Analytical Research, 2019)
Tizanidine hydrochloride is an Imidazoline derivative which acts as agonist on centrally located α 2 receptors and this leads to myotonolytic effects on skeletal muscle. The dosage of 2-4 mg is given. Tizanidine's bioavailability is about 34-40% and its half-life is about 2.5 hours. It is subjected to a metabolism in the first step (approximately 95% of the dose) of the liver which allows the imidazole state, the aromatic system and the sulphur atom to be oxidated. This leads to reduced bioavailability and a bitter taste of Tizanidine hydrochloride. The application of various carriers including β-cyclodextrin, mannitol and povidone to enhance the bioavailability of the flavor and to mask the strong dispersion technique. Results of prepared solid Tizanidine HCL dispersions by the solvent method of evaporation, including solubility, melting point determination, uniformity in drug content, entrapment efficiency and studies of in vitro-dissolution were discussed. Characterization in solid state was done by various analytical techniques such as FT-IR studies. Ultimately, by comparing in different ratios all the formulations i.e.,F1-F9 with Tizanidine HCL, povidone, β-cyclodextrin & Mannitol. By Solvent evaporation method at the end of 90 min with drug release of 93.99, Formulation F9 containing β-cyclodextrin (1:3) showed better results. This is why it was selected optimized formulation. Through comparing the release kinetic studies of Tizanidine HCL with zero order and first order , the better formulations are replaced by the kinetic studies of first order.